IMPROVING THE ECONOMY OF PESANTREN THROUGH WASTE PROCESSING WITH THE GREEN ECONOMY MODEL IN DARUN NAJAH ISLAMIC COLLAGE LUMAJANG - Ainul Yaqin; Abdul Rokhim; Ahmadiono (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Many people have implemented waste management through the green economy model, yielding beneficial results, particularly for environmental conservation plans. Islamic boarding schools make it possible to produce quite a lot of waste from the students' daily needs. We conducted this study at the Darun Najah Islamic College in Lumajang. The Darun Najah Islamic College in Lumajang implements a waste management program that utilizes waste for economically valuable purposes, specifically the production of processed products, where waste processing is a key production factor. This research focuses on green economy-based waste processing processes and explores their potential to enhance the economy at the Darun Najah Islamic College in Lumajang. This research aims to create a manageable green economy model for Islamic boarding schools, offering economic value and potential. We used qualitative research and a case study approach to explore waste management practices within a green economy model, which significantly and massively improves the Islamic boarding school economy. We collected data through interviews, observation, and documentation. The research results show that the green economy model at the Darun Najah Islamic College in Lumajang uses three steps, namely, reduce, reuse, and recycle. The Darun Najah Islamic College in Lumajang has a significant potential for waste management to become a new product. This study concludes that environmentally friendly Islamic College not only require technological adaptation and management but also require a deep understanding and commitment to religious values that support environmental sustainability. This research makes a significant contribution to the development of sustainable business models in Islamic College, as well as enriching the literature regarding the integration of religious teachings and modern economic practices.